(untitled) (Experimental biology, 2018)
Caddis flies of Kazakhstan are studied rather poorly. As for 2018, 151 species of 59 genera of 17 families among 14548 species of World fauna are known in Kazakhstan. The largest numbers of species are found in mountain and submontane regions of Tian Shan and Altay (Southern and Eastern Kazakhstan), caddis flies of Central and Northern Kazakhstan are studied much worse. Nowadays are known 22 caddis flies species from Central Kazakhstan and 13 species from North Kazakhstan. Caddis flies research in 2015-2016 made it possible to expand the list of caddis Central Kazakhstan to 1 species, list caddis North Kazakhstan – to 4 species. Molanna albicans (Zetterstedt, 1840) and Grammotaulius nitidus (Mueller, 1764) are recorded for Kazakhstan at first. Detected species are limnophilous and widely distributed in Holarctic, Transpalearctic and sometimes Transpalearctic-Oriental Regions. Comparative analysis showed, that Central and Northern Kazakhstan are uniform in the biogeographical aspects, which are close to Southern trans-Ural (West Palearctic). The resemblance to South-Western Siberia is much lower. The article is illustrated by original photographs of the male genitalia of these species. Key words: Trichoptera, fauna, male genitals, Central Kazakhstan, North Kazakhstan.